suPAR, a Circulating Kidney Disease Factor - Wei, Changli; Spear, Ryan; Hahm, Eunsil; Reiser, Jochen (Frontiers in Medicine, 2021)
Urokinase plasminogen activator receptor (uPAR) is a multifaceted, GPI-anchored three-domain protein. Release of the receptor results in variable levels of soluble uPAR (suPAR) in the blood circulation. suPAR levels have been linked to many disease states. In this mini-review, we discuss suPAR as a key circulating molecule mediating kidney disease with a particular focus on differently spliced isoforms.